The urgency of sexual education in early childhood: A portrait of children's curiosity towards their authority - Nisa, Uswatun (Aṭfālunā Journal of Islamic Early Childhood Education, 2024)
This study aims to explore the urgency of sexual education in early childhood that arises from children's curiosity about their authority. The informants in this qualitative research are five teachers and five parents from 5 different early childhood education units in Banjarmasin, South Kalimantan, Indonesia. The data were purposively selected based on the criteria of parents with girls or boys aged 5-6 years, heterogeneous background cluster, and integrated Islamic preschool. Data analysis using Miles and Huberman includes the process of data reduction, display, and verification with Jean Piaget's cognitive development theory and its relevance to Sigmund Freud's psychosexual. The results showed that sexual education for early childhood is urgent because children have a high curiosity about their authority. Children are formed from various stages in their psychosexual process, which corresponds to the level of their thinking ability. The sexual knowledge will determine the direction of the child's personality and behavior in the future. Parents and teachers can establish partnerships to create a basic sexual education program for children while developing socialization skills, independence, self-confidence, and positive self-concept and fostering children's religious and moral values. Although this study is still limited to a small scale, it can be an initial illustration for other regions in designing sexual education programs for children, and further program evaluation can be carried out.